Preparation, Characterization and Antimicrobial Activity of Chitosan Schiff Base / Polyvinyl Alcohol Nanocomposite - Eelaf N. Talib (Journal of Global Pharma Technology, 2019)
Schiff base of chitosan with Para-Dimethyl aminobenzaldehyde /PVA-Ag Nanocomposite have been prepared as antimicrobial polymer. The prepared chitosan Schiff base and chitosan Schiff base / PVA-Ag nanocomposite were characterized by FT-IR, SEM analysis and biological activity. The nanocomposite showed good activity against different types of bacteria.Keywords: Chitosan, Chitosan Schiff base, Ag-nanocomposite, antimicrobial polymer.